Student and teacher related variables as determinants of secondary school students academic achievement in chemistry - Francis A. Abuseji, (penerbit ukm, 2007)
The study constructed and tested a model for providing a causal explanation of secondary school achievements in chemistry in terms of student variables – gender, study habit, mathematical ability and teacher’s variables – gender,age, qualification and years of experience. An ex-post facto design was adopted for the study. The population was made up of all senior secondary school year two (SSII) students and their teachers in Epe and Ibeju-Lekki local government areas of Lagos state, Nigeria. However, six and four schools were used in the two local government areas respectively. Four sets of instrument were used; these were, (i) Personal Data Questionnaire for Teachers (PDQT) (ii) Study Habit Inventory (SHI) (iii) Mathematical Ability Test (MAT) and (iv) Chemistry Achievement Test (CAT). The results showed that 7.60% of the variability in students’ achievement in chemistry (X8) was accounted for by all the seven predictor variables when taken together. It was also revealed that only four of the variables-teacher age (X1), teacher gender (X2), qualification (X3) and experience (X4) had direct causal effect on student’s achievement in chemistry (X8). Recommendations based on the importance of these variables were then highlighted.